Pengaruh Hoaks Deepfake terhadap Persepsi Keputusan Sosial pada Masyarakat Dewasa Menengah di Era Post-Truth - Fatih Rizqi Jatikusuma Handoyo; Rendra Widyatama (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of artificial intelligence technology, especially in the field of deepfakes, amplifies the spread of digital hoaxes that can impact people's perceptions and social decisions in the post-truth era. This study aims to analyze the influence of exposure to deepfake hoaxes, concerns about deepfakes, and attitudes toward digital information on perceptions of social decisions in the middle-aged adult group. This study employed a quantitative approach with a survey of 82 respondents obtained using purposive sampling techniques and analyzed using multiple linear regression. The results indicate that exposure to deepfake hoaxes, attitudes toward digital information, and concerns about deepfakes significantly influence perceptions of social decisions. With an R value of 0.852, this study proves that the model can explain 85.2% of all independent variables in terms of the dependent variable. This finding reinforces previous research regarding the need for digital literacy and media education to improve public skills and awareness in verifying and addressing disinformation spread through artificial intelligence.